2021
DOI: 10.1002/adfm.202109170
|View full text |Cite
|
Sign up to set email alerts
|

Scaling of the Thermally Induced Sign Inversion of Longitudinal Spin Seebeck Effect in a Compensated Ferrimagnet: Role of Magnetic Anisotropy

Abstract: The authors report on a systematic investigation of the longitudinal spin Seebeck effect (LSSE) in a GGG(Gd3Ga5O12)/GdIG(Gd3Fe5O12)/Pt film series exhibiting an in‐plane magnetic easy axis with a compensation temperature (TComp) that decreases from 270 to 220 K when decreasing GdIG film thickness from 272 to 31 nm, respectively. For all the films, the LSSE signal flips its sign below TComp. The authors demonstrate a universal scaling behavior of the temperature dependence of LSSE signal for the GdIG films arou… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
26
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 24 publications
(29 citation statements)
references
References 60 publications
2
26
0
Order By: Relevance
“…The bilayer structure consisting of ferrimagnetic insulator Y3Fe5O12 (YIG) and Pt is known as the hallmark system for LSSE. [9][10][11][12][13] Apart from insulating iron garnets, 14 insulating spinel ferrites e.g., CoFe2O4, 15 have also emerged as another promising class of magnetic insulators for LSSE. Over the years, research has shown that the observation of LSSE is not only restricted to magnetic insulators, including ferrimagnetic and antiferromagnetic insulators 9,16 , but it has also been observed in ferromagnetic metals, 4 half-metallic ferromagnets, e.g., mixed valent manganites 17 and ferromagnetic semiconductors, e.g., GaMnAs 18 .…”
Section: Introductionmentioning
confidence: 99%
“…The bilayer structure consisting of ferrimagnetic insulator Y3Fe5O12 (YIG) and Pt is known as the hallmark system for LSSE. [9][10][11][12][13] Apart from insulating iron garnets, 14 insulating spinel ferrites e.g., CoFe2O4, 15 have also emerged as another promising class of magnetic insulators for LSSE. Over the years, research has shown that the observation of LSSE is not only restricted to magnetic insulators, including ferrimagnetic and antiferromagnetic insulators 9,16 , but it has also been observed in ferromagnetic metals, 4 half-metallic ferromagnets, e.g., mixed valent manganites 17 and ferromagnetic semiconductors, e.g., GaMnAs 18 .…”
Section: Introductionmentioning
confidence: 99%
“…Such a special temperature dependence and spin colossal magnetoresistance (Figure S3, Supporting Information) exclude side effects such as spin mixing conductance, the manipulation of which should occur in whole temperature ranges. The typical V SSE –μ 0 H loops of YIG/Cr 2 O 3 /Pt at 245 K with positive and negative electric fields are depicted in Figure c (The curves are shifted vertically for clarity), presenting a similar shape with the hysteresis curve of YIG (Figure d), confirming that the magnon spin current is generated from YIG. The V SSE signal of +4 kV cm –1 is remarkably larger than that of −4 kV cm –1 , suggesting the enhanced electric field-controlled spin current transport efficiency through Cr 2 O 3 via ferroelastic strain.…”
mentioning
confidence: 61%
“…In particular, for LSSEs, the spatial directions of Js and σ in NM are, respectively, along the applied ∇T and equilibrium magnetization meq near the interface, meaning that the output field satisfies the relationship EISHE ∝ ∇T × meq. The LSSE voltage can therefore extract the projection of the (surface) magnetization on the direction along the magnet/metal interface, allowing to reveal the in-plane magnetic orientation (within ℓm) and also magnetic anisotropies (56,57,60,61,120,121).…”
Section: Sse As Probe Of Magnetic Order and Domainsmentioning
confidence: 99%